Simulation of a solar domestic water heating system using a time marching model - Bojic, Milorad; Kalogirou, Soteris A.; Petronijevi, K. (My University, 2002)
This paper presents the modelling and simulation of a solar water heating system using a time marching model. The results of simulations performed on an annual basis for a solar system, constructed and operated in Yugoslavia, which provides domestic hot water for a four-person family are presented. The solar water heater consists of a flat-plate solar collector, a water-storage tank, an electric heater, and a water-mixing device. The mathematical model is used to evaluate the annual variation of the solar fraction with respect to the volume of the storage tank, demand hot water temperature required, difference of this temperature and preset storage tank water temperature, and consumption profile of the domestic hot water demand. The results of this investigation may be used to design a solar collector system, and to operate already designed systems, effectively. The results for a number of designs with different storage tank volumes indicate that the systems with greater volume yield higher solar fraction values. The results additionally indicate that the solar fraction of the system increases with lower hot water demand temperature and higher differences between the mean storage water and the demand temperatures. However, when a larger storage tank volume is used, the solar fraction is less sensitive to a variation of these operation parameters.
Keywords: Solar collector; Storage tank; Electric heater; Modeling; Simulation